Comparison of synovial fluid, urine, and serum ion levels in metal‐on‐metal total hip arthroplasty at a minimum follow‐up of 18 years. Issue 9 (20th May 2014) - Lass, Richard; Grübl, Alexander; Kolb, Alexander; Stelzeneder, David; Pilger, Alexander; Kubista, Bernd; Giurea, Alexander; Windhager, Reinhard
ABSTRACT Diagnosis of adverse reactions to metal debris in metal‐on‐metal hip arthroplasty is a multifactorial process. Systemic ion levels are just one factor in the evaluation and should not be relied upon solely to determine the need for revision surgery. Furthermore, the correlation between cobalt or chromium serum, urine, or synovial fluid levels and adverse local tissue reactions is still incompletely understood. The hypothesis was that elevated serum and urine metal‐ion concentrations are associated with elevated local metal‐ion concentrations in primary total hip arthroplasties (THA) and with failure of metal‐on‐metal articulations in the long‐term. In our present study, we evaluated these concentrations in 105 cementless THA with metal‐on‐metal articulating surfaces with small head diameter at a minimum of 18 years postoperatively. Spearman correlation showed a high correlation between the joint fluid aspirate concentration of cobalt and chromium with the serum cobalt (r = 0.81) and chromium level (r = 0.77) in patients with the THA as the only source of metal‐ions. In these patients serum metal‐ion analysis is a valuable method for screening. In patients with more than one source of metal or renal insufficiency additional investigations, like joint aspirations are an important tool for evaluation of wear and adverse tissue reactions in metal‐on‐metal THA. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:1234–1240, 2014.